Influencing factors of radiation-induced skin injury induced by hypofractionated radiotherapy with simultaneous integrated boost for early breast cancer patients after breast-conserving surgery - SHAO Ruiyu, WANG Jianting, WANG Xiaohong (Xin yixue)
Objective To analyze the influencing factors of radiation-induced skin injury induced by hypofractionated radiotherapy with simultaneous integrated boost in patients with early breast cancer after breast-conserving surgery. Methods Medical records of 182 patients with early breast cancer who were treated with hypofractionated radiotherapy with simultaneous integrated boost after breast-conserving surgery in Tangshan People’s Hospital from June 2021 to June 2023 were retrospectively analyzed. According to the severity of radiation dermatitis， they were divided into the control group （0 degree， n = 60）， mild group （1-2 degree， n = 62）， and severe group （≥ 3 degree， n = 60）. Clinical data of patients among three groups were compared. The influencing factors of radiation-induced skin injury were identified by multivariate Logistic regression analysis. Results There were no statistically significant differences in age， menstrual status， tumor marker levels， pathological grading， capecitabine use， CD3+ T and CD8+ T cell apoptosis rates among three groups （all P > 0.05）. The proportion of patients with body mass index （BMI） ≥28 kg/m2， T2 stage， triple-negative breast cancer and CD4+ T cell apoptosis rate in the mild and severe groups were higher than those in the control group， and the data in the severe group were higher than those in the mild group （all P < 0.05）. Multivariate Logistic regression analysis showed that BMI≥28 kg/m2 [OR （95%CI） = 2.413 （1.206-4.829）]， tumor stage T2 [OR （95%CI） = 3.830（1.768-8.296）]， triple-negative breast cancer [OR （95%CI） = 2.399（1.188-4.844）] and CD4+ T lymphocyte apoptosis rate [OR （95%CI） = 1.526（1.218-1.912）] were the risk factors for radiation-induced skin injury （all P < 0.05）. Conclusion BMI， T stage， CD4+ T cell apoptosis rate and triple-negative breast cancer are the main risk factors of radiation-induced skin injury in patients with early breast cancer undergoing hypofractionated radiotherapy with simultaneous integrated boost after breast-conserving surgery， which can affect the degree of radiation-induced skin injury.